2012
DOI: 10.4028/www.scientific.net/amr.616-618.162
|View full text |Cite
|
Sign up to set email alerts
|

Shear Rheological Properties of Sericite-Greisen Phyllite

Abstract: Creep and aging behavior, the inherent mechanical properties of rocks, are important evidences for analysis of geological structure and prediction of long term stability of rock mass. In this study, laboratory tests are carried out to investigate the shear creep occurring along the schistosities of sericite-greisen phyllite, and a rheological constitutive model of phyllite is established subsequently. On this basis, a fitting analysis of the test data using Burgers model is made, thus providing a reference for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Yang et al discussed the standard of soft rock as a filler and studied the influence of the weathering degree and rock structure on weathered soft rock through rock strength test and particle-breaking test [20]. In related work, the physical and mechanical properties of phyllite and determined the engineering characteristics such as the mineral composition and mechanical strength of phyllite [21][22][23][24]. Xiong and Xu conducted an experimental study on the water content and particle size distribution of weathered phyllite subgrade and concluded that phyllite-filled subgrade can meet the requirements for the stable settlement of the subgrade and the sharp drop in strength after the immersion of phyllite.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al discussed the standard of soft rock as a filler and studied the influence of the weathering degree and rock structure on weathered soft rock through rock strength test and particle-breaking test [20]. In related work, the physical and mechanical properties of phyllite and determined the engineering characteristics such as the mineral composition and mechanical strength of phyllite [21][22][23][24]. Xiong and Xu conducted an experimental study on the water content and particle size distribution of weathered phyllite subgrade and concluded that phyllite-filled subgrade can meet the requirements for the stable settlement of the subgrade and the sharp drop in strength after the immersion of phyllite.…”
Section: Introductionmentioning
confidence: 99%
“…Zhongjin Wang [4] made a deepen study on roadbed filler classification. Guangming Reng [5]'s research on phyllite rock rheological analysis and calculation provided a theoretical basis. Bingwei Pang [6] considered the mountainous area highway subgrade filling weathered rock engineering characteristics and construction key technology.…”
Section: Introductionmentioning
confidence: 99%